2022
DOI: 10.3389/fped.2022.826600
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Human Adenovirus, Astrovirus, and Sapovirus Among Outpatient Children With Acute Diarrhea in Chongqing, China, 2017–2019

Abstract: ObjectiveTo investigate the epidemiology of human adenovirus (HAdV), human astrovirus (HAstV), and sapovirus (SaV), children with acute diarrhea in Chongqing, China from 2017 to 2019 were enrolled. Improved surveillance could provide better guidance for diarrhea prevention.MethodsBetween 2017 and 2019, fecal specimens were collected from children <14 years of age presenting with acute diarrhea for treatment at the outpatient department of the Children’s Hospital, Chongqing Medical University. Human HAdV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…HAdV enteric types F40/41 accounted for nearly half of sequenced samples, with a massive predominance of type F41 compared to type F40. Our data are in line with worldwide findings, which appears to be a global trend in regards to HAdV genotype distribution among AGE cases 22 , 23 , 38 , 57 , 59 . Previous molecular epidemiological studies conducted in Brazil also demonstrated the predominance of type F41, accounting for more than half of all sequenced samples 29 31 , 34 , 60 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HAdV enteric types F40/41 accounted for nearly half of sequenced samples, with a massive predominance of type F41 compared to type F40. Our data are in line with worldwide findings, which appears to be a global trend in regards to HAdV genotype distribution among AGE cases 22 , 23 , 38 , 57 , 59 . Previous molecular epidemiological studies conducted in Brazil also demonstrated the predominance of type F41, accounting for more than half of all sequenced samples 29 31 , 34 , 60 .…”
Section: Discussionsupporting
confidence: 92%
“…Among the non-enteric HAdV, our study found HAdV species C and B with the second and third highest prevalence, respectively. Previous studies performed in Brazil and other developing countries have reported similar results for non-enteric HAdV, with specie C being the most prevalent and specie A, B and D alternating as the second most prevalent 22 , 23 , 29 , 32 , 38 . Moreover, despite an increasing number of studies attributing the detection of non-enteric HAdV types in AGE stool samples as a possible gastroenteritis causative agent 13 , 22 , 23 , 40 , the significance of their detection remains unclear.…”
Section: Discussionsupporting
confidence: 70%
“…HAdV F40/41 genotypes co-circulated similar to what has been reported elsewhere (7)(8)(9)(10). In previous studies, the proportion of F40 in sequenced HAdV-F positive samples was lower compared to compared to F41 (3-36% vs 11-97%) partly due to the higher genetic diversity in the F41 genotype that is hypothesised to enable it to outcompete F40 potentially via immune escape (7)(8)(9)(10)(11). A similar finding of lower F40 diversity was observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The genome of HAdV-F40/41 is approximately 35,000 basepairs (6). Previously there have been HAdV studies in Ethiopia, Albania, China, India and Brazil following which the researchers have reported a higher prevalence in HAdV-F41 cases compared to F40 (7)(8)(9)(10)(11). Coinfections between F40 and F41, and F41 and C5 were reported in Brazil and Ethiopia (7,10).…”
Section: Introductionmentioning
confidence: 99%
“…HAstV-1 and 2 were circulating during the study period from 2016 to 2021 and HAstV-4 was detected in 2018-2020, whereas HAstV-5 was observed in 2017 only, at all study sites. HAstV-5 was also detected in Thailand during 2000-2011 and 2017-2020, and in China in 2017-2018, with a low proportion [33,[37][38][39]. However, this HAstV-5 genotype was also found in Nigeria from 2015 to 2017 [40].…”
Section: Discussionmentioning
confidence: 93%